Expression of Differentiated Functions in Hepatoma Cell Hybrids: Reappearance of Tyrosine Aminotransferase Inducibility after the Loss of Chromosomes - Weiss, Mary C. (1971)
Hybrids from a cross of rat hepatoma cells with diploid epithelial cells from rat liver have been studied with respect to karyotype and expression of two functions limited to the hepatoma parent: high level of the enzyme tyrosine aminotransferase (EC 2.6.1.5; L-tyrosine:2-oxoglutarate aminotransferase) and its inducibility with steroid hormones. The hybrids that contain the complete chromosomal complements from both parents show low enzyme activity and no inducibility. One hybrid clone, and all of its derivatives, which have lost 30-40% of the chromosomes initially present, show enzyme inducibility. Induction of tyrosine aminotransferase in the hepatoma and hybrid cells responds similarly to inhibition by cycloheximide and actinomycin D, and to steroid concentration. The enzymes from induced and noninduced hepatoma cells and from induced hybrid cells are similar in heat sensitivity and intracellular distribution; those from noninduced hybrid and diploid rat epithelial cells are different.